2015
DOI: 10.1016/j.redox.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Annexin II-dependent actin remodelling evoked by hydrogen peroxide requires the metalloproteinase/sphingolipid pathway

Abstract: Actin remodeling is a dynamic process associated with cell shape modification occurring during cell cycle and proliferation. Oxidative stress plays a role in actin reorganization via various systems including p38MAPK. Beside, the mitogenic response evoked by hydrogen peroxide (H2O2) in fibroblasts and smooth muscle cells (SMC) involves the metalloproteinase (MMPs)/sphingomyelinase 2 (nSMase2) signaling pathway. The aim of this work was to investigate whether this system plays a role in actin remodeling induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…; Cinq‐Frais et al . ). Given the role of the SMPD3 pathway in exosome biogenesis, we tested if SMPD3 is involved in exosome secretion by VSMCs and found that inhibition of SMPD3 reduced exosome production (Trajkovic et al .…”
Section: Exosomes Released From Vascular Smooth Cells Mediate Calcifimentioning
confidence: 97%
“…; Cinq‐Frais et al . ). Given the role of the SMPD3 pathway in exosome biogenesis, we tested if SMPD3 is involved in exosome secretion by VSMCs and found that inhibition of SMPD3 reduced exosome production (Trajkovic et al .…”
Section: Exosomes Released From Vascular Smooth Cells Mediate Calcifimentioning
confidence: 97%
“…Upregulation of AnxA2 in response to H 2 O 2 -induced oxidative stress has been reported for several cell types ( Tanaka et al, 2004 ; Kim et al, 2011 ; Madureira et al, 2011 ) and its phosphorylation is also increased under these conditions ( Tanaka et al, 2004 ; Matsuda et al, 2006 ). A recent study concluded that H 2 O 2 -induced Tyr23 phosphorylation of AnxA2 occurs through the metalloproteinase and sphingolipid pathways ( Cinq-Frais et al, 2015 ). The protein has also been shown to reside in the nucleus, where it contributes to the protection of DNA in cells exposed to H 2 O 2 and other genotoxic agents ( Madureira et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…ANXA2 belongs to the calcium-conducting annexin family, which has been reported to activate MAPK signaling and promote metastasis in tumor cells. Tyrosine phosphorylation (Tyr23) of ANXA2 was required for ERK1/2 activation [ 30 , 41 , 42 ]. In RalA-overexpressing MDA231 cells, we observed that ANXA2 knockdown indeed reduce p-ERK1/2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ANXA2, an accessory protein that belongs to the calcium-conducting annexin family [ 25 ], is highly expressed in breast tumor tissues [ 26 ]. Tyr23 Phosphorylation of ANXA2 by Src tyrosine kinase is an important post-translational modification of ANXA2, and p-ANXA2 has significant effects on ERK signal activation, EMT, and metastasis in tumor cells [ 27 30 ]. However, little is known regarding the interaction between RalA, ANXA2 and Src in BC.…”
Section: Introductionmentioning
confidence: 99%